ANNA: uma ferramenta para apoio à tomada de decisão para a gestão administrativa da Universidade Federal de Roraima - Silva, Adayanne Tobias da (2022)
The present work deals with the creation of the ANNA virtual tool, identified by a specific brand with regional expressions, in which the peculiarities of the state of Roraima were used for its creation, using the Macuxi indigenous language to define the word ANNA, which means to know in Portuguese, the in order to contribute to the dissemination of scientific knowledge produced at the Federal University of Roraima (UFRR). The research is qualitative, descriptive and applied, and used bibliographical research, semi-structured interviews with former UFRR managers, software development, creation of a brand and was evaluated by specialist researchers. It is expected that this work will help the administrative management of the Federal University of Roraima, be it the superior administration or the coordination of centers and courses, allowing the scientific works produced to be stored and consulted more easily. The use of the tool can contribute to the development of the institution through the registration of research aimed at improving the institution, showing the need and importance of applying this tool through the evaluation carried out by researchers from the institution.